Application of the Kaizen Method in Efforts to Maintain the Sustainability of Springs in Indonesia - Muhammad, Ilham; Putri, Maya Aiko Salsabila; Karimah, Husna Latifatul; Prastiwi, Gita Putri; Fitriyah, Nur Himmatul; Taniady, Vicko (International Journal Labs, 2022)
Indonesia represents about 6% of the world's water sources. This shows that Indonesia has abundant water resources. However, the facts show that most areas of Indonesia experience a shortage of clean water supplies. This is because the spring can be lost within a certain period if there is no planning to maintain its availability. The solution offered is to fulfil clean water needs with the Kaizen method. Kaizen is a 5S philosophy that includes Seiri, Seinton, Seiso, Seiketsu, and Shitsuke. This study aims to review the application of Kaizen methods and their sustainability to be applied in Indonesia. The methods used in this study are descriptive observational are aimed at describing and describing phenomena of a scientific and human engineering nature. The results of this study are packaged in the House Model. The House Model is a tool used by an organization using a concept built to transform into action. Some activities in the house model are tailored to meet the needs of partners and further increase the efficiency and effectiveness of the programs being implemented. The program also has good sustainability in community aspects, regulations, and government.